1998
DOI: 10.1073/pnas.95.3.1172
|View full text |Cite
|
Sign up to set email alerts
|

HLA class I-specific inhibitory receptors in human T lymphocytes: Interleukin 15-induced expression of CD94/NKG2A in superantigen- or alloantigen-activated CD8+ T cells

Abstract: and CD8؉ cells expressed CD94, the simultaneous expression of NKG2A (i.e., the other component of the CD94͞NKG2A inhibitory NKR) was confined to CD8 ؉ cells. Similar data were obtained in T cell populations activated in mixed lymphocyte cultures in the presence of IL-15. The expression of CD94͞NKG2A led to an impairment of allo-specific cytolytic activity by mixed lymphocyte culture-derived T cell populations or clones. Remarkably, cytolysis could be restored by the addition of anti-CD94 mAb, i.e., by masking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
169
3

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(184 citation statements)
references
References 34 publications
10
169
3
Order By: Relevance
“…This has been achieved upon antigenic stimulation, both in vitro and in vivo [13,14]. In vitro, this phenomenon is potentiated by cytokines, such as IL-2, IL-10, IL-12, IL-15 and TGFb [15][16][17][18]. These observations are consistent with the in vivo expression of NKR on antigen-experienced T cells.…”
Section: Introductionsupporting
confidence: 53%
“…This has been achieved upon antigenic stimulation, both in vitro and in vivo [13,14]. In vitro, this phenomenon is potentiated by cytokines, such as IL-2, IL-10, IL-12, IL-15 and TGFb [15][16][17][18]. These observations are consistent with the in vivo expression of NKR on antigen-experienced T cells.…”
Section: Introductionsupporting
confidence: 53%
“…In the bone marrow of mice, expression of NK1.1 and Ly49 molecules have been shown to be associated with memory T cells (23). Studies performed in humans have described activated CD8 ϩ T cells that possess NKR-P1C (24) or inhibitory NK cell receptors such as p58.2 (25-27), NKB-1 (27,28), and CD94/NKG2A (25,29,30). Similar T cells have also been found in HIV-infected patients (31).…”
Section: Cd8␤ ϩ Nk11 ϩ Cells Are Not Conventional Nkt Cellsmentioning
confidence: 63%
“…Second stimulation of CMV-specific NKR Ϫ T cells with stimulatory cytokines and cognate peptide did not result in acquisition of KIR. Many other deliberate attempts to induce KIR expression in T cells in vitro have failed, although Mingari et al have reported the induction of CD94:NKG2A (50). Recently, down-regulation of KIR was reported on NKR ϩ T cell clones that were deprived of specific Ag (51).…”
Section: Discussionmentioning
confidence: 99%